2010
DOI: 10.1016/j.arthro.2009.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Bone-to-Bone Fixation Enhances Functional Healing of the Porcine Anterior Cruciate Ligament Using a Collagen-Platelet Composite

Abstract: Purpose-The purpose of this study was to determine if providing bony stabilization between the tibia and femur would improve the structural properties of an "enhanced" ACL repair using a collagen-platelet composite when compared to the traditional (Marshall) suture technique.Methods-Twelve pigs underwent unilateral ACL transection and were treated with sutures connecting the bony femoral ACL attachment site to the distal ACL stump (LIGAMENT group), or to the tibia via a bone tunnel (TIBIA group). A collagen-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 22 publications
2
103
0
Order By: Relevance
“…Murray et al 23 tested a similar hypothesis that boneto-bone (femur-to-tibia) suture fixation at the time of primary ACL repair would improve stabilization and lead to improved healing in a Yorkshire pig model with midsubstance ACL transection. They compared animals that underwent suture anchor primary repair with animals that underwent repair with transtibial suture augmentation.…”
Section: Preclinical Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Murray et al 23 tested a similar hypothesis that boneto-bone (femur-to-tibia) suture fixation at the time of primary ACL repair would improve stabilization and lead to improved healing in a Yorkshire pig model with midsubstance ACL transection. They compared animals that underwent suture anchor primary repair with animals that underwent repair with transtibial suture augmentation.…”
Section: Preclinical Studiesmentioning
confidence: 94%
“…Several authors investigated the role of stability during ACL repair. [20][21][22][23] Seitz et al 20 showed that stability obtained through an internal strut augmentation using a 3-mm polyethylene terephthalate (PET) band passed through femoral and tibial bone tunnels improved histologic evidence of healing when compared with the non-augmented repair construct. In their mountain sheep model, serial gross and histologic assessments were performed at varying time intervals up to 52 weeks.…”
Section: Preclinical Studiesmentioning
confidence: 98%
“…For all knees, a Kessler suture using No. 1 Vicryl 1 was placed in the tibial stump of the ACL to repair the transected ligament [20,36,37]. Femoral (4.5 mm) and tibial (2.4 mm) tunnels were then drilled in standard positions for ACL reconstruction with the tibial tunnel exiting in the center of the tibial attachment and the femoral tunnel placed at the center of the femoral ACL attachment site.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A 2.4-mm drillpin was then used to make a tunnel in the tibia with use of a drill guide (Acufex Director Drill Guide; Smith and Nephew) to ensure that the entrance into the joint was just medial to the anterior cruciate ligament footprint. The tibial tunnel would later serve to secure the repair sutures directly to the tibia as previously described 9,10 . The resorbable sutures bridging the femur and tibia (as shown in purple in Figure 1) served as a temporary stent within the knee.…”
Section: Surgical Proceduresmentioning
confidence: 99%